TEACHING READING COMPREHENSION USING PRE-VIEWING TECHNIQUE - Rosmiati, Neng Dewi (IKIP Siliwangi, 2019)
Reading is one of the basic communicative skills, but it has very complex process. It can be said that reading is a process in which the reader gets message from the author in the written from. The objectivities of this research entitled “Teaching Reading Comprehension Using Previewing technique” was to find out whether or not the previewing as pre reading technique can improve students’ reading comprehension. The population was all the students grade XI of Ma Muslimin Cijenuk in the academic years 2017-2018,while the sample of this research was 34 students of XI science established through random technique. The Research used quantitative method. The instruments used in this research were pretest and posttest. The techniques in analyzing the data were using SPSS version 21. The result of data analysis showed that the value of the t-value is 21.185 is bigger than t-table at level 5% 2.042, it means that the hypothesis null is rejected. The results of the study show that teaching reading using previewing technique in second grade of MA Muslimin Cijenuk is able to improve students’ reading comprehensions. Keywords: Reading Comprehension, Previewing Technique